Heterogeneous network real-time video transmission ARQ and FEC mode selection method based on QOE - YANG MEI; CHEN PINGPING; YU PINGPING; CHEN FENG (2022)
The invention relates to a QOE-based heterogeneous network real-time video transmission ARQ and FEC mode selection method, and provides a real-time video transmission system which comprises a sending end and a receiving end, and comprehensively considers end-to-end delay of video receiving and occupied extra transmission bandwidth parameters by defining QOE; the receiving end calculates the current QOE state in real time and feeds back the QOE to the sending end, and the sending end adjusts the sending mode according to the received QOE and the current network state. According to the invention, different message transmission modes are selected in different network environments according to the QOE of the user, and the problems of packet loss and congestion of the wireless network are effectively solved. 本发明涉及一种基于QOE的异构网络实时视频传输ARQ与FEC模式选择方法，提供一实时视频传输系统，包括发送端和接收端，通过定义QOE，综合考虑接收视频的端到端延时、所占用的额外传输带宽参数；接收端实时计算当前的QOE状态，并将QOE反馈至发送端，发送端根据收到的QOE以及当前的网络状态调整发送模式。本发明根据用户的QOE在不同的网络环境下选择不同的报文传送模式，有效解决无线网络丢包、拥塞问题。